2023
DOI: 10.3389/fimmu.2022.1071223
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling the tumor immune microenvironment with oncolytic viruses expressing miRNAs

Abstract: MiRNAs (miRNA, miR) play important functions in the tumor microenvironment (TME) by silencing gene expression through RNA interference. They are involved in regulating both tumor progression and tumor suppression. The pathways involved in miRNA processing and the miRNAs themselves are dysregulated in cancer. Consequently, they have become attractive therapeutic targets as underscored by the plethora of miRNA-based therapies currently in pre-clinical and clinical studies. It has been shown that miRNAs can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The TME can alter the miRNA profile of tumor-associated macrophages, cancer-associated fibroblasts, and other host cells. It was reported that miRNAs play important functions in TME by silencing gene expression through RNA interference [65]. The altered miRNAome is propagated to various cellular compartments within the TME via exosomes secreted by cells loaded with oncomirs.…”
Section: Discussionmentioning
confidence: 99%
“…The TME can alter the miRNA profile of tumor-associated macrophages, cancer-associated fibroblasts, and other host cells. It was reported that miRNAs play important functions in TME by silencing gene expression through RNA interference [65]. The altered miRNAome is propagated to various cellular compartments within the TME via exosomes secreted by cells loaded with oncomirs.…”
Section: Discussionmentioning
confidence: 99%